Headache OSCE Part 3: A 22-Year-Old Woman Presents to the Emergency Department After Waking Up With the Sudden Onset of a Severe Headache - Diana Barratt; Daniel Segui; Fauzia Nausheen (Association of American Medical Colleges, 2013)
Abstract Introduction This 15-minute objective structured clinical exam (OSCE) requires that the examinee take a detailed headache history from a standardized patient, generate an initial differential diagnosis, request and interpret diagnostic tests, and defend the final diagnosis. Methods This OSCE features a 22-year-old obese female presenting with headache. Her young age of onset brings into question the common primary headache disorders, including migraine and tension headache. Her obesity and fertility bring into question vision-threatening and life-threatening secondary headache disorders such as pseudotumor cerebri (idiopathic intracranial hypertension) and venous sinus thrombosis. Criteria for passing and a grading system have been established. Remediation plans are prescribed, depending on the type of error made by the examinee. Results Forty-four medical students completed this assessment. Seventy-three percent of students passed the OSCE. Sixteen percent of students required remediation because they did not order a lumbar puncture. After writing an essay on the indications for lumbar puncture, these students received a score of 80. Eleven percent of students failed the OSCE because they misdiagnosed the patient. After writing an essay comparing and contrasting the correct diagnosis with the erroneous diagnosis, failing students received a score of 75. The scores ranged from 75-98, with a mean of 90. Normative data for each section are detailed in the Facilitator's Guide. Discussion We recommend spending 5 additional minutes for structured feedback. This OSCE can be altered by having the patient present with signs and symptoms of potentially life-threatening neurological conditions, such as increased intracranial pressure and subarachnoid hemorrhage.